The Correlation between Body Mass Index, Physical Activity and Blood Pressure with Quality of Life in Elderly Hypertension - Andi Astillawati; Edi Purwanto; Lukman Nulhakim (Formosa Journal of Science and Technology, 2023)
Hypertension is a global and national health problem known as the silent killer," which continues to increase. Community-based preventive promotion efforts are a strategy for controlling hypertension, especially in the elderly, through Posbindu activities and routine health check-ups. This study aims to determine the relationship between body mass index, physical activity, and blood pressure and the quality of life of hypertensive elderly people in the working area of ​​the UPT Puskesmas Tanjung Redeb. This research is a type of correlational quantitative research with a cross-sectional design. The results showed that there was a significant relationship between BMI (p-value 0.629), physical activity (p-value 0.000), and blood pressure (p-value 0.013) and quality of life in the elderly. Good quality of life is accompanied by an increase in BMI to near normal, physical activity to near normal, and blood pressure to near normal.